DETERMINAN IMPLEMENTASI AKUNTANSI AKRUAL TERHADAP AKUNTABILITAS SEKTOR PUBLIK : PENDEKATAN TEORI INSTITUSIONAL - Rohana Maqdliyan (Universitas Lambung Mangkurat, 2022)
Ministries and government agencies are required to follow the grand design of the National Bureaucratic Reform (RB) and the provisions of the International Federation of Accountants (IFAC) in implementing accrual accounting reforms to strengthen Public Financial Management (PFM). The application of accrual accounting in Indonesia in forming of financial statements has been carried out since 2015. However, this rule is still debated regarding the need and importance of accrual accounting in the public sector. This condition is due to technical ambiguity, costs, and failure of implementation in some countries. This study aims to present a literature review on the factors causing the effectiveness of accrual accounting implementation in the public sector from the perspective of institutional theory and to obtain a conceptual model for further research related to its effectiveness on transparency and accountability of public sector performance. This study uses content analysis from previous research based on the approach used. The results indicate that there are complex patterns of several factors that significantly influence the formation of an effective model. Institutional and social pressure factors that may affect and complicate the implementation process include pressure from institutions, government, audit boards, political will, regulations/rules, commitment to change management, the culture of transparency, technology, management support, and training, but the individual factors include knowledge, skills, and qualifications show contradictory things. This condition is possible due to environmental differences between countries. Therefore, the suggestion for future research is to reveal the complexity of the pattern and its effectiveness by exploring the variables related to institutional, social, and individual in forming the administrative model of accrual accounting application to the transparency and accountability of the public sector. Institusi kementerian dan lembaga pemerintah dituntut mengikuti grand design Reformasi Birokrasi (RB) Nasional dan ketetapan dari International Federation of Accountant (IFAC) dalam penerapan reformasi akuntansi akrual untuk penguatan Public Financial Management (PFM). Penerapan akuntansi akrual di Indonesia dalam penyusunan laporan keuangan telah dilakukan sejak 2015. Namun, aturan ini masih menjadi perdebatan mengenai kebutuhan dan pentingnya akuntansi akrual di sektor publik. Hal ini karena adanya ambiguitas teknis, biaya dan kegagalan implementasinya di beberapa negara. Penelitian ini bertujuan untuk menyajikan tinjauan literatur tentang faktor penyebab efektifitas implementasi akuntansi akrual di sektor publik ditinjau dari perspektif teori institusional serta untuk mendapatkan model konseptual penelitian selanjutnya terkait efektifitasnya terhadap transparansi dan akuntabilitas kinerja sektor publik. Penelitian ini menggunakan analisis konten/isi yang diidentifikasi dari penelitian sebelumnya berdasarkan pendekatan yang digunakan. Hasil penelitian menunjukkan terdapat kompleksitas pola dari beberapa faktor yang signifikan berpengaruh hingga terbentuk model yang efektif. Faktor tekanan dari institusional dan sosial yang dimungkinkan berpengaruh dan memperumit proses implementasi antara lain tekanan dari institusi, pemerintah, dewan audit, kemauan politik, regulasi/aturan, komitmen perubahan manajemen, budaya transparansi, teknologi, dukungan manajemen, pelatihan. Sedangkan faktor individu yang mencakup pengetahuan, ketrampilan, kualifikasi menunjukkan hal yang kontradiktif. Kondisi ini dimungkinkan karena perbedaan lingkungan antar negara. Oleh karena itu, saran untuk penelitian berikutnya yaitu mengungkap kompleksitas pola dan efektifitasnya dengan melakukan eksplorasi variabel terkait intitusional, sosial, dan individu dalam membentuk model administratif penerapan akuntansi akrual terhadap transparansi dan akuntabilitas sektor publik.